2021
DOI: 10.3390/sym13091664
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Vibration Foam Rolling Warm-Up on Jump and Flexibility Asymmetry, Agility and Frequency Speed of Kick Test Performance in Taekwondo Athletes

Abstract: The effect of asymmetry on flexibility and jump in taekwondo athletes and the influence of vibration foam rolling on asymmetry and frequency speed of kick test has not been examined. This study examined the effects of three warm-up protocols on subsequent sports performance in elite male taekwondo athletes. Fifteen elite male taekwondo athletes (20.63 ± 1.18 years) completed three warm-up protocols in a randomized order: general warm-up [GW], GW with vibration foam rolling [GW + VR], and GW with double VR for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
(39 reference statements)
0
9
0
1
Order By: Relevance
“…However, despite the above studies showed significant results, there are also studies reporting no significant improvements for interventions of SMR in terms of maximum force or power testing [ 12 , 57 , 60 , 61 , 62 , 66 , 70 , 73 ]. There have been no effects on several variables, such as vertical jump (height, power, and/or speed), 90°/s isokinetic knee extension, contraction time, and isometric force after SMR exercises [ 74 , 75 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, despite the above studies showed significant results, there are also studies reporting no significant improvements for interventions of SMR in terms of maximum force or power testing [ 12 , 57 , 60 , 61 , 62 , 66 , 70 , 73 ]. There have been no effects on several variables, such as vertical jump (height, power, and/or speed), 90°/s isokinetic knee extension, contraction time, and isometric force after SMR exercises [ 74 , 75 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 98%
“…In this systematic review, 25 studies in total were identified [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ], examining the use of different SMR techniques before and after exercise and also as a recovery method. Each study applied different exercise protocols, using various treatments, application times, and measures and assessing different results, which made the selection of results a challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Teakwondo da galibiyet büyük oranda bacak kuvvetine, çevikliğe, esnekliğe ve anaerobik alaktik güce bağlıdır. 12 Bu branşta; hızlı dönüş yeteneği, çabukluk, çeviklik ve denge gibi fitness bileşenleri önemlidir çünkü hücum ve savunma manevraları rakiplerin hareketlerine göre yapılır ve atakların en az %90'ı ayak tekniklerini içerir. Postüral dengenin bozulması vücut instabilitesine, pasif kas-iskelet sistemine aşırı yüklenmeye ve buna bağlı rahatsızlıklara, ağrılara ve düşmelere sebep olabilir.…”
Section: Abstract Objectiveunclassified
“…Lykesas et al [18] designed a warm-up routine using Greek traditional dance, and found no difference in flexibility performance and better performance in agility tests compared to dynamic stretching in immediate response. Chen et al [19] added a vibrating foam roller to a traditional warm-up routine and found that this combination significantly improved performance on the hexagon test and the frequency speed of kick test (FSKT). Pojskić et al [20] used prolonged intermittent low-intensity isometric exercise as a warm-up program and found that when 30 % body weight resistance was applied, the improvements of speed and agility were similar to dynamic stretching.…”
Section: Introductionmentioning
confidence: 99%